2018
DOI: 10.1007/s11259-018-9717-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different avian influenza (H5) vaccination regimens in layer chickens on the humoral immune response and interferon-alpha signalling immune marker

Abstract: Avian influenza (AI) vaccines are widely used to control and eliminate the ongoing avian influenza virus epidemic in Egypt. A strict vaccination policy with inactivated AI vaccines has been widely applied, however the virus still circulating, evolving and causing great negative impact to the poultry sector in Egypt. Therefore, an updated poultry vaccination policy using different vaccine technologies might be valuable as an innovative additional control strategy of AIV in Egypt. In the present study, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…They involve manufacturing recombinant subunit vaccines, based on hemagglutinin (HA), the surface glycoprotein of influenza viruses that is capable of eliciting neutralizing antibodies (10). As a result, anti-H5N1 virus vaccines, such as Volvac® B.E.S.T AI + ND for chickens (11) and Panblok for humans (12) have been produced. An important feature of HA-based vaccines is their compatibility with the differentiating infected from vaccinated animals (DIVA) strategy (13).…”
Section: Introductionmentioning
confidence: 99%
“…They involve manufacturing recombinant subunit vaccines, based on hemagglutinin (HA), the surface glycoprotein of influenza viruses that is capable of eliciting neutralizing antibodies (10). As a result, anti-H5N1 virus vaccines, such as Volvac® B.E.S.T AI + ND for chickens (11) and Panblok for humans (12) have been produced. An important feature of HA-based vaccines is their compatibility with the differentiating infected from vaccinated animals (DIVA) strategy (13).…”
Section: Introductionmentioning
confidence: 99%
“…Most recombinant HVT-vectored vaccines showed effective protection in vaccinated chickens when challenged with homologous AIV. It is known that protection can be correlated with HI serological titers, and the HI serological titer results in these studies demonstrated that antigen-specific antibodies could be induced by these recombinant HVT viruses (Gao et al, 2011 ; Li et al, 2011 ; Kapczynski et al, 2015 , 2016 ; Hamad et al, 2018 ; Liu et al, 2019 ). Apart from this, the recombinant HVT virus could induce cellular immunity, which is also involved in the protection of chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the Volvac ® B.E.S. T AI + ND vaccine containing the H5 HA protein of baculovirus-expression system origin has been positively evaluated by efficacy trials in commercial chickens [13]. In general, recombinant DNA technology has been widely explored to obtain influenza virus HA protein, as exemplified by rH5-E. coli [10,12].…”
Section: Discussionmentioning
confidence: 99%